ANALISIS MANFAAT SERTIFIKASI INDONESIAN ORGANIC FARM CERTIFICATION (INOFICE) TERHADAP KEBERLANJUTAN USAHATANI KOPI ORGANIK DI KECAMATAN AIR HITAM KABUPATEN LAMPUNG BARAT - Meri Fatmalasari; Fembriarti Erry Prasmatiwi; Novi Rosanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research purposed to analyze the benefits of Indonesian Organic Farm Certification (INOFICE) toward the development of coffee farm sustainability from economic dimension, environmental dimension and social dimension.  This research was conducted at Air Hitam sub district Lampung Barat district.  Sample of research are 30 farmers each from certified farmer and non certified farmer.  Economic benefits was analyzed through on farming analysis by counting productivity, cost efficiency and income then was tested with t test to know if there any difference.  The economic, environmental and social benefits were analyzed using Mann Whitney U test.  The result showed that (1) INOFICE certification had not given benefits toward of coffee farm sustainability.  Certified farmers who has been sustainable on economic, environmental dan social were 73,33.% while noncertified farmers were 96,67% categories in sufficiently sustainable on economic, environemental and social.  (2) INOFICE certification had not given economic benefits like increasing of productivity and income, but it gave benefit like increasing cost efficiency. (3) INOFICE certification gave benefits in sustainable coffee farm application in term of economic, environmental and social. The application of sustainable coffee farm in economic, environmental and social form was higher significantly on farmers certified than nonsertified farmers. Key words : advantage, coffee , certification, INOFICE, sustainable